Contact parameter analysis and calibration in discrete element simulation of rice straw - Jia, Honglei; Deng, Jiayu; Deng, Yanling; Chen, Tianyou; Wang, Gang; Sun, Zaijin; Guo, Hui (International Journal of Agricultural and Biological Engineering, 2021)
Discrete element method was used to study and analyze the interaction between rice straws and between rice straw and agricultural machinery parts, thereby providing a scientific basis for post-harvest paddy field processing. Calibrations of rice straw-rice straw, rice straw-agricultural machinery part contact parameters (collision recovery coefficient, static friction coefficient and rolling friction coefficient) constitute an important prerequisite for the discrete element research process. In this study, the collision recovery coefficients of rice straw-steel and rice straw-rice straw were 0.230 and 0.357, respectively, which were calibrated by the collision method. The static friction coefficient and rolling friction coefficient of rice straw-steel were 0.363 and 0.208 respectively, which were calibrated by the inclined plate method and the slope method. The static friction coefficient and rolling friction coefficient of rice straw-rice straw were 0.44 and 0.07, respectively, which were calibrated by the split cylinder method. The paired t-test showed insignificant differences between calibration parameter simulation results and the physical test values (p>0.05). Taking the angle of repose that reflecting rice straw flow and friction characteristics as the evaluation index, the verification tests of the above calibration values indicated that the simulated angle of repose has no significant difference from the physical test value (p>0.05). The side plate lifting test on rice straw of different lengths showed no significant difference between the simulated angle of repose and the physical test value (p>0.05). This study can provide a basis for contact parameters choice in discrete element simulation analysis with rice straw-rice straw and rice straw-agricultural machinery parts as the research object. The calibration method can provide a reference for the contact parameter calibration of other crop straws.Keywords: rice straw, discrete element simulation, contact parameter, parameter calibration, angle of reposeDOI: 10.25165/j.ijabe.20211404.6435Citation: Jia H L, Deng J Y, Deng Y L, Chen T Y, Wang G, Sun Z J, et al. Contact parameter analysis and calibration in discrete element simulation of rice straw. Int J Agric & Biol Eng, 2021; 14(4): 72–81.